2014
DOI: 10.1186/1556-276x-9-656
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and magnetic functionalization of graphene oxide as a route to enhance its biocompatibility

Abstract: The novel approach for deposition of iron oxide nanoparticles with narrow size distribution supported on different sized graphene oxide was reported. Two different samples with different size distributions of graphene oxide (0.5 to 7 μm and 1 to 3 μm) were selectively prepared, and the influence of the flake size distribution on the mitochondrial activity of L929 with WST1 assay in vitro study was also evaluated. Little reduction of mitochondrial activity of the GO-Fe3O4 samples with broader size distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 62 publications
3
27
0
1
Order By: Relevance
“…The inclusion of PPy and the chemical nature of the GO/PPy composites were confirmed by FTIR, as shown in Figure . The FTIR spectrum of GO is almost identical to the previously reported results by Rajagopalan et al and Urbas et al, having the characteristic peaks of GO that correspond to alkoxy, epoxy, and carboxyl functional groups (the stretching vibration of OH groups at the broad peak at 3410 cm −1 , C = O stretching vibration mode of carboxyl group at 1730 cm −1 , C = C bond skeletal vibration at 1610 cm −1 , carboxyl C‐O deformation at 1230 cm −1 , and C‐O stretching vibration mode of the alkoxy groups at 1080 cm −1 ) . The FTIR spectrum of PPy shows typical characteristic peaks (stretching vibration of N–H bonds 3400 cm −1 , stretching vibration of C = C bonds at 1560 cm −1 , vibration of the pyrrole rings at 1190 cm −1 , in‐plane vibrations of C–H bonds at 1045 cm −1 , C‐C deformation at 930 cm −1 , and out‐of‐plane vibrations of the C–H bonds at 790 cm −1 ) .…”
Section: Resultssupporting
confidence: 86%
“…The inclusion of PPy and the chemical nature of the GO/PPy composites were confirmed by FTIR, as shown in Figure . The FTIR spectrum of GO is almost identical to the previously reported results by Rajagopalan et al and Urbas et al, having the characteristic peaks of GO that correspond to alkoxy, epoxy, and carboxyl functional groups (the stretching vibration of OH groups at the broad peak at 3410 cm −1 , C = O stretching vibration mode of carboxyl group at 1730 cm −1 , C = C bond skeletal vibration at 1610 cm −1 , carboxyl C‐O deformation at 1230 cm −1 , and C‐O stretching vibration mode of the alkoxy groups at 1080 cm −1 ) . The FTIR spectrum of PPy shows typical characteristic peaks (stretching vibration of N–H bonds 3400 cm −1 , stretching vibration of C = C bonds at 1560 cm −1 , vibration of the pyrrole rings at 1190 cm −1 , in‐plane vibrations of C–H bonds at 1045 cm −1 , C‐C deformation at 930 cm −1 , and out‐of‐plane vibrations of the C–H bonds at 790 cm −1 ) .…”
Section: Resultssupporting
confidence: 86%
“…Peaks at 1550, 1460, and 3442 cm −1 are referred to C-C, C-N, and N-H stretching vibrations of poly pyrole. The obtained results are in accordance with the literatures [24,29,30]. The X-ray diffraction pattern of NGO and NGPPC was investigated (Figure 2b).…”
Section: Ngppc Characterizationsupporting
confidence: 90%
“…Another method for enhancing GO biocompatibility is functionalization with nanoparticles. In our previous study [24], we showed that GO modification with magnetite nanoparticles resulted in improved biocompatibility with mouse fibroblasts (L929) compared to unmodified GO. A summary of these in vitro studies is presented in Table 1.…”
Section: Biocompatibility Of Graphene and Graphene Oxidementioning
confidence: 96%